Utilization of Zakat Funds on The Welfare Dimensions of The Poor In Aceh Besar (Baitul Mal Mustahik Case Study) - Utari, Ulya; Sari, Nurma; Amri, Amri (El-Qish: Journal of Islamic Economics, 2021)
This study aims to analyze the effect of zakat funds utilization on the dimensions of the welfare of the poor in Aceh Besar. This research uses a quantitative approach by multivariate analysis (Manova) method. Data was collected by interviewing and distributing questionnaires to mustahik the Baitul Mal Aceh, using the Probability Sampling method and using the Quota Sampling Model. The utilization of zakat funds is reviewed in the scope of categories of types of businesses (agriculture, trade, and services), while the welfare dimension is measured by several variables (food, clothing, Education, Health, and Savings). Findings. The results showed that the type of business had a significant effect on the dimensions of welfare. Agriculture was the type of business with the highest level of welfare, followed by services and trade.